How Unfair is the Inequality of Wage Earnings in Russia? : Estimates from Panel Data - Tiwari, Sailesh; Lara Ibarra, Gabriel; Narayan, Ambar (World Bank, Washington, DC, 2015)
This paper attempts to determine the extent to which inequality in wage earnings in the Russian Federation is unfair. Unlike other similar attempts that can, at best, produce a lower bound on the estimate of the share of inequality that is unfair, this paper exploits the longitudinal nature of the data to come up with a lower bound as well as an upper bound. The upper bound is further refined to take into account the indirect effect of circumstances at birth (gender, parental wealth, etc.) on effort. Results show that the upper bound on the inequality of opportunity may be three to four times the measured lower bound and significantly higher for females than males in the sample. Finally, comparison with the United States and Germany show that although total inequality is lower in Russia, the share of unfair inequality is distinctly larger. The markedly large explanatory role of extraneous factors, such as gender and parental characteristics, in wage inequality calls for a close examination of governments’ efforts to address inequities in the labor market.